THESE FIRES CAN BE PREVENTED PLEASE SUPPORT H.R. 293, THE FIRE SAFE CIGARETTE ACT. - MOAKLEY JJ (Tufts Archival Research Center, 2007)
Letter from Congressman Joseph Moakley to the members of congress asking for support for his bill, H.R. 293, the Fire Safe Cigarette Act. Claims that this bill takes the necessary steps to combat accidental fires from cigarettes. Attaches a list of current supporters.